PH-dependent micellar properties of edible biosurfactant steviol glycosides and their oil-water interfacial interactions with soy proteins. (May 2022) - Yang, Yunyi; Zhang, Juyang; Liu, Yang; Wu, Linhe; Li, Qing; Xu, Mengyue; Wan, Zhili; Ngai, To; Yang, Xiaoquan
Abstract: The natural sweetener steviol glycosides (STE) have been shown to be an effective biosurfactant for formulation of food emulsions. In this work, we first investigated the impact of pH on the micellar self-assembly of STE, and then evaluated the interfacial and macroscopic emulsion properties of the mixtures of STE with soy protein isolate (SPI) at different pH values (3.0 and 7.0). The results obtained show that as an edible bolaform surfactant, STE is a highly pH-sensitive system, showing interesting pH-dependent interfacial and emulsifying behaviors, which are found to strongly affect its oil-water interfacial interactions with SPI as well as the emulsion properties of the STE-SPI mixtures. Particularly, at low STE concentrations (0.1–0.4 wt%, below critical micelle concentration (CMC)), the adsorption kinetics of mixtures at pH 7.0 is mainly dominated by the STE-SPI complex, forming the interface with a plateau in the elasticity. In contrast, at pH 3.0, the simultaneous adsorption of STE and the STE-SPI complex dominates the formation of interface, resulting in a lower initial interfacial tension and a less viscoelastic film. These interfacial behaviors endow the emulsions prepared by the mixtures with an improved emulsifying ability. On the other hand, at high STE concentrations (0.8 and 1 wt%, above CMC), for the mixtures at pH 7.0, the preferential interfacial adsorption of STE over the complex leads to the formation of a simple interface mainly covered by STE. Contrastly, the interfaces at pH 3.0 are still complex and dominated simultaneously by STE and STE-SPI complex. However, the poor emulsifying capacity of STE at pH 3.0 greatly disturbs the emulsifying properties of the mixtures, resulting in the large oil droplets and the consequent phase separation of emulsions. Graphical abstract: Image 1 Highlights: Natural steviol glycosides (STE) can be used as an edible bolaform biosurfactant. STE and STE-SPI mixtures exhibit pH-sensitive interfacial and emulsifying behaviors. The mixtures at pH 7.0 have a more apparent synergistic effect in interfacial stabilization. The poor emulsifying properties of mixtures at pH 3.0 are due to the disturbance of STE.